Have paper, will travel: Participation at A.C.J.S. annual meetings - Lab, Steve P. (American journal of criminal justice, 1982)
Graduate criminology and criminal justice faculty participation at the 1979–81 Academy of Criminal Justice Sciences annual meetings are examined. Results show that institution prestige, not faculty productivity, is the but predictor of meeting participation. It is suggested that further attention be devoted to profroessional concerns in order to understand the development of a academic criminology.